2018
DOI: 10.2472/jsms.67.190
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Prediction of Spatial Deterioration of Airport Runway

Abstract: Maintenance problem for infrastructures such as bridge, road, airport, etc., attracts keen interest in modern Japan. We have to cope with repair and maintenance for infrastructures with limited financial resources. In airport pavements, repair works are restricted by daily flight operation, so that efficient maintenance planning is required. In this paper, we try to model deterioration of an existing airport runway, which is composed of 100 units. PRI (Pavement Rehabilitation Index) for each unit is obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 2 publications
1
77
1
Order By: Relevance
“…On one side, the study of energy transport through mesoscopic or atomic systems has found applications in disparate systems: from solid state devices [1,2] to light harvesting complexes [3][4][5][6]; from ultra-cold atomic systems [7][8][9] to trapped ions [10][11][12]. On the other side, coherent manipulation of energy is at the core of quantum thermodynamics, whose aims include the understanding of the emergence of thermodynamic laws from quantum mechanics [13][14][15][16][17][18][19][20][21] and the design of thermal machines made with quantum devices [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…On one side, the study of energy transport through mesoscopic or atomic systems has found applications in disparate systems: from solid state devices [1,2] to light harvesting complexes [3][4][5][6]; from ultra-cold atomic systems [7][8][9] to trapped ions [10][11][12]. On the other side, coherent manipulation of energy is at the core of quantum thermodynamics, whose aims include the understanding of the emergence of thermodynamic laws from quantum mechanics [13][14][15][16][17][18][19][20][21] and the design of thermal machines made with quantum devices [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Equation(21) shows that the counter-diabatic field vanishes at the initial and final moments, i.e., | ( ) }is identical to the adiabatic eigenbasis s s 0 , 0 ñ ñ   {| ( ) | ( ) }, which satisfies the presumption of the two-point measurement scheme[25,[39][40][41]. In figures 2(c) and (d), the evolution of B t ( ) with the operation time T=25 ns is plotted explicitly.…”
mentioning
confidence: 77%
“…. Based on the two-point measurement scheme [25,[39][40][41], the probability distribution function of a quantum work at time t is written as…”
Section: Statistics Of Sta Workmentioning
confidence: 99%
See 1 more Smart Citation
“…(24), we need to perform Gaussian path integrals over each bath variable q n (z) in Eq. (20) which are in general of the form,…”
Section: Summary and Discussionmentioning
confidence: 99%